2020
DOI: 10.22159/ajpcr.2020.v13i7.37756
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Modification, and Characterization of Natural Polymers Used in Transdermal Drug Delivery System: An Updated Review

Abstract: The modified/regulated drug delivery system helps to sustain the delivery of the drug for a prolonged period. The modified drug delivery system is primarily aimed at ensuring protection, the effectiveness of the drug, and patient compliance. The transdermal drug delivery system (TDDS) falls within the modified drug delivery system, in which the goal is to deliver the drug at a fixed dose and regulated rate through the skin. Polymers are the backbone of the framework for providing transdermal systems. The polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…In contrast, F5 (high carrageenan proportion) and F6 (high locust bean gum proportion) showed a lower cumulative lycorine release. Carrageenan and locust bean gum are often used as a thickening and stabilizing agent ( 44 ) which has revealed that an increase in the concentration of locust bean gum decreases the cumulative percent drug release with a sustained release ( 45 46 ). Kaur et al .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, F5 (high carrageenan proportion) and F6 (high locust bean gum proportion) showed a lower cumulative lycorine release. Carrageenan and locust bean gum are often used as a thickening and stabilizing agent ( 44 ) which has revealed that an increase in the concentration of locust bean gum decreases the cumulative percent drug release with a sustained release ( 45 46 ). Kaur et al .…”
Section: Discussionmentioning
confidence: 99%
“…The mucilage is separated from water by adding alcohol, typically absolute ethanol, as it provides a higher yield than ethanol: water mixture precipitates faster. Ethanol is also preferred because it is eco-friendly and FDA-approved [ 32 , 74 ]. Other solvents like acetone and methanol are also used for mucilage precipitation.…”
Section: Methods Of Isolation and Physicochemical Parameters Of Natur...mentioning
confidence: 99%
“…Later, the dried mucilage was separated from the seeds by passing it through № 18 mesh, and the seed husks were removed by winnowing. Some people prefer to freeze-dry the mucilage instead of heating it ( Figure 10 ) [ 32 , 74 ].…”
Section: Methods Of Isolation and Physicochemical Parameters Of Natur...mentioning
confidence: 99%
“…A slow stir with a magnetic stirring was then added 20% w/w of the total weight of the polymers to the homogenous dispersion. The consistent dispersion was cast on the previously cast Polyvinyl alcohol backing membrane and air-dried at room temperature 6 . Formulations were removed from the mould.…”
Section: Preparation Of the Transdermal Patchesmentioning
confidence: 99%